Suitability Analysis of Pal Beach (Indonesia) as an Emerging Coastal Recreational Destination - Kontu, Tommy Meiky; Lintong, Oktavianus; Oroh, Dannie Rieshard Stephen (Turizam, 2024)
This study evaluates the suitability of Pal Beach in North Sulawesi, Indonesia, as a recreational beach tourism destination. Ten key parameters influencing beach tourism are assessed, including water depth, beach type and width, seabed material, vegetation, water clarity, currents, harmful marine life and freshwater availability. Results classify Pal Beach as ’Very Suitable’ with a score of 2.82. The beach boasts features like shallow coastal waters, sandy white shores, ample width, good water visibility, coconut trees and gentle slopes catering to visitors. However, strong currents exceeding ideal speeds, the presence of stonefish and sea snakes, and limited onsite freshwater pose notable challenges needing mitigation for its sustainability. By analyzing tourism viability while identifying environmental constraints, this assessment contributes insights to guide the integrated management of emerging recreational destinations in Indonesia based on globally accepted principles of responsible, sustainable development.